Effects of immersion depth on super-resolution properties of index-different microsphere-assisted nanoimaging. (5th February 2018) - Zhou, Yi; Tang, Yan; He, Yu; Liu, Xi; Hu, Song
Abstract: In related applications of microsphere-assisted super-resolution imaging in biomedical visualization and microfluidic detection, liquids are widely used as background media. For the first time, we quantitatively demonstrate that the maximum irradiances, focal lengths, and waists of photonic nanojets (PNJs) will logically vary with different immersion depths (IMDs). The experimental observations also numerically illustrate the trends of the lateral magnification and field of view (FOV) with the gradual evaporation of ethyl alcohol. This work can provide exact quantitative information for the proper selection of microspheres and IMD for the high-quality discernment of nanostructures.